Analysis of The Implementation of Government Accounting Standards in the Preparation of Operational Reports to the Government of BPKD Bengkulu Province - Arnita Anggraini; Oni Yulianti; Herlin Herlin (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the suitability of the preparation of the Operational Report on the Government of the Regional Financial Management Agency of Bengkulu Province with PSAP No. 12 concerning Accrual-Based Operational Reports. The results of this study are expected to provide input, especially in the field of public sector accounting related to Accrual-Based Government Accounting Standards. This research was conducted at the Bengkulu Provincial Government Financial Management Agency. The data in this study are document and interview data. The data was obtained from the Bengkulu Provincial Financial Management Agency Government in the form of an Operational Report for the 2020 fiscal year. The data analysis technique used was a qualitative analysis method, which is a method that describes in advance the recording, recognition, and reporting of income and expenses to the Government of the Financial Management Agency. Bengkulu Province which was then adjusted to PSAP No.12 concerning Accrual-Based Operational Reports. The results showed that the preparation of the Operational Report on the Government of the Bengkulu Province Regional Financial Management Agency was in accordance with PSAP No. 12. This can be seen from the recording, recognition, and reporting of income and expenses in the preparation of the Operational Report in accordance with PSAP No. 12 concerning accrual-based Operational Reports.